2014
DOI: 10.3389/fnhum.2014.00197
|View full text |Cite
|
Sign up to set email alerts
|

Low and then high frequency oscillations of distinct right cortical networks are progressively enhanced by medium and long term Satyananda Yoga meditation practice

Abstract: Meditation proficiency is related to trait-like (learned) effects on brain function, developed over time. Previous studies show increases in EEG power in lower frequency bands (theta, alpha) in experienced meditators in both meditation states and baseline conditions. Higher gamma band power has been found in advanced Buddhist meditators, yet it is not known if this occurs in Yoga meditation practices. This study used eLORETA to compare differences in cortical source activity underlying scalp EEG from intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 59 publications
2
23
0
5
Order By: Relevance
“…Meditation has further been associated with an increase in telomerase activity (Jacobs et al, 2011), 5-hydroxyindole-3-acetic acid (5-HIAA) and serotonin levels, as well as a decrease in vanillic-mandelic acid (VMA), each of which may engage the relaxation response rather than the fight-or-flight response (Bujatti & Biederer, 1976). Finally, Satyananda Yoga meditation has been associated with an increase in low frequency EEG activity (Thomas, Jamieson, & Cohen, 2014), which could be responsible for an improvement in hyperarousal and other PTSD symptoms. Satyananda Yoga was selected for use in the present study because the classes incorporate the benefits of these four practices in a holistic approach so that all PTSD symptom clusters are addressed in the most integral way.…”
Section: Introductionmentioning
confidence: 99%
“…Meditation has further been associated with an increase in telomerase activity (Jacobs et al, 2011), 5-hydroxyindole-3-acetic acid (5-HIAA) and serotonin levels, as well as a decrease in vanillic-mandelic acid (VMA), each of which may engage the relaxation response rather than the fight-or-flight response (Bujatti & Biederer, 1976). Finally, Satyananda Yoga meditation has been associated with an increase in low frequency EEG activity (Thomas, Jamieson, & Cohen, 2014), which could be responsible for an improvement in hyperarousal and other PTSD symptoms. Satyananda Yoga was selected for use in the present study because the classes incorporate the benefits of these four practices in a holistic approach so that all PTSD symptom clusters are addressed in the most integral way.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found by the study of Thomas et al [23] that the networks greatly expanded during meditation practice to include homologous regions of the left hemisphere. It may be speculated that this may be true for the present study as well.…”
Section: Discussionmentioning
confidence: 68%
“…The above studies [18,23] demonstrated changes in the right inferior frontal gyrus and temporal region. The activation of the rMTG reported in the present study is in contrast to the findings of a report [24] which measured the performance of participants during an fMRI adapted Stroop word-color task.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Effect of yoga meditation practice and EEG wave was analyzed and it was observed that immediate yoga meditators have greater source of activity in low frequencies particularly theta and alpha wave during mental calculation. Advance yoga meditators showed greater activity in high frequencies (beta and gamma) in all conditions (Thomas, 2014). Other researcher reported that EEG based improvements in cognitive abilities like attention and working memory with meditation practice .…”
Section: Improvement Of Brain Functions Through Meditationmentioning
confidence: 85%